Relatório de estágio do ensino da prática supervisionada: crescer para ser - Araújo, Luísa (2015)
This report pertains to Pre-school Education and Primary Education. It offers an overview of the pedagogical practice developed in a Pre-school context, with a heterogeneous group, and in the context of Primary Education, working with a second grade class. In both groups there was an identification and development of a priority intervention area, the area of personal and social education, which addressed cooperation, socialization and respect for others. Considered a very important area of development, we sought solutions in educational literature to contribute effectively in the education of our children, particularly in those areas. Several authors consider the playful methodologies as promoters of cognitive strategies, social and moral development. Contemplating the opinion of some authors cited throughout this work, we introduced in the practice developed these methodologies in order to contribute to the development of these skills. This report presents some examples of activities with these methodologies. Troughout the reporting and analysis in both education ranges, this study confirms the importance of fun and learning games for the development of the children. However, the results obtained by instruments of skills assessment, both in the Pre-school context and in Primary Education, were not significant to the point of considering that games and playful activities promote the development of social skills. On the other hand, considering the theoretical view that points in that direction, we believe that the systematic application of these methodologies could result in better outcomes. Although we have not achieved the expected results, it is believed, as these authors do, that these methods should be adopted.